Digital Marketing Strategy and Its Influence on Consumer Purchasing Decisions at Kopi Kenangan Surabaya: The Mediating Role of Brand Awareness - Fidel Jonathan Kontarya; Daniel Joel Immanuel Kairupan; Dewi Mustikasari Immanuel (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2025)
Advances in digital technology have driven significant changes in the way consumers access information and make purchasing decisions. This study aims to examine the influence of digital marketing in purchasing decisions, considering brand awareness as a mediating variable. The research approach used was quantitative with a descriptive associative method. Primary data was collected through questionnaires administered to 110 respondents who met the criteria used in this study was Partial Least Square Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS version 4 software. The results of the analysis indicate that digital marketing has a positive and significant influence on brand awareness and purchasing decisions. Furthermore, brand awareness was also shown to have a significant influence on purchasing decisions and can act as a mediating variable, bridging the relationship between digital marketing and purchasing decisions. These findings indicate that appropriately implemented digital marketing strategies can increase consumer awareness of a brand, ultimately impacting consumer purchasing decisions.